Intergenerational transmission of powerty in Finland in the 1990s - Airio, Ilpo; Moisio, Pasi; Niemelä, Mikko (University of Turku, Department of Social Policy, 2004)
Abstract (1 s.).
Keywords: lama; köyhyys